The Effect of Electronic Module Simulation (EMS) Injury Handling on Student Preparedness in Injury Handling at SMP Muhammadiyah 8 Surakarta - Dani Saputro, Sutiyo; Anissa Cindy Nurul Afni (PT Inovasi Pratama Internasional, 2023)
Wounds from mishaps in the school climate by and large happen in the outer muscle framework and should be dealt with rapidly and properly. Injury will cause dying, bone disfigurement or inability and even passing. Support dressing alleviation can be performed by any prepared layman. One of the laypeople prepared at school is an understudy who has gotten essential crisis instruction. Nursing fundamental instruction is given through the Adolescent Red Cross (PMR) extracurricular. There should be an expansion in treating breaks in understudies with online reenactments utilizing the Electronic Recreation Module (EMS). The motivation behind this study was to decide the impact of Electronic Module Reproduction (EMS) of Injury Dealing with on Understudies' Readiness in Taking care of Wounds at SMP Muhammadiyah 8 Surakarta. This research of exploration is a quantitative report utilizing a semi exploratory examination plan with a pre-post test without control which is completed via doing a mediation in one gathering without a correlation. The examination test was 43 understudies of SMA Al Islam 1 Surakarta. Information assortment was done two times at the time before treatment and after treatment. Information examination was performed utilizing the Wilcoxon test. The consequences of the Wilcoxon test on readiness when the mediation got a p worth of 0.000 so there was an impact of the Electronic Module Reproduction (EMS) of Injury The executives on Understudy Readiness in Dealing with Wounds at SMP Surakarta. There is an Impact of Electronic Reenactment Module (EMS) Injury Taking care of on Understudies' Readiness in Dealing with Wounds at SMP Muhammadiyah 8 Surakarta with a p worth of 0.000.